Language Variation Used by Food Vloggers on TikTok and Its Influence on Audience Language Use - Mutia Putri; Sholihatul Hamidah Daulay (STKIP Subang, 2026)
This study investigates language variation employed by food vloggers on TikTok and examines its subsequent influence on how audiences communicate in digital spaces. As short-form video content continues to reshape sociolinguistic norms among Indonesian youth, food vloggers have emerged as influential language agents who blend Bahasa Indonesia with English, deploy culinary-specific slang, and adopt trending expressions that resonate with younger audiences. Drawing on a qualitative descriptive approach, this research collected data from TikTok food vlogs, including video transcripts, captions, comments, and hashtags, from five prominent Indonesian food vlogger accounts throughout 2023 to 2024. The analysis was guided by sociolinguistic frameworks proposed by Labov (1972), Hymes (1974), Fishman (1972), and Trudgill (2000). Findings reveal four dominant patterns of language variation: code switching between Bahasa Indonesia and English, code mixing within single utterances, the use of culinary slang, and the appropriation of prestige language to construct social identity. Expressions such as